PENGARUH RELAKSASI OTOT PROGRESIF DENGAN MEDIA VIDEO ANIMASI TERHADAP STRES REMAJA SELAMA PANDEMI COVID-19 - Ariestini, Dewik Prisilia; Swedarma, Kadek Eka; Utami, Putu Ayu Sani (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024DO - 10.24843/coping.2024.v12.i04.p13, 2025)
Stress that occurs in adolescents during the pandemic Covid-19 has an impact on the learning process carried out. The application of progressive muscle relaxation through education with animated video is one technique that can be used to reduce stress conditions experienced by adolescents. The aim of this study was to determine the effect of progressive muscle relaxation on adolescent stress. This research is a quasi-experimental study with a one group pretest-posttest design. The sample of this study were 74 students in grade X as participants with a simple random sampling technique. Data collection was carried out in the pre-test using a teenage stress level questionnaire, followed by giving progressive muscle relaxation interventions with animated video for 8 times within 2 weeks and ending with giving a post-test again about adolescent stress. Data were analyzed using Wilcoxon test. The result of the pre-test showed that most of the 51.4% experienced severe stress. Then, the post test to measure stress among adolescents was performed and the post-test results mostly 79.7% experienced moderate stress, p value = 0.000 (p <0.05). It was conclusion that application of progressive muscle relaxation with animated video has an effect on adolescent stress during the pandemic Covid-19. Researchers recommend doing progressive muscle relaxation techniques as a form of action to manage stress that is easy and simple that can be done at home with a frequency of exercise 2 times a day.